FAKTOR YANG MEMPENGARUHI IBU BERSALIN DENGAN PARAJI DI DUSUN PENYIMAHAN DESA PULAU PALAS KABUPATEN INDRAGIRI HILIR - Nurul Indah Sari (STIKES HUSADA GEMILANG, 2018)
Childbirth is a process of spending the conceptus (fetus, uri) that can live in the world. Delivery help by paraji (traditional birth attendant) is often done in a traditional way. The high maternal mortality rate (MMR) in Indonesia which one of them is due to the low coverage of delivery assistance by health personnel. The maternal and infant mortality rates are 129 of 100 thousand births and 11.7 deaths of 100 live births. The purpose of this study was to analyze the factors affecting the mothers did the labor with the help of paraji on Penyimahan, Pulau Palas, Indragiri Hilir. This study is descriptive analytic quantitative approach. The number of samples in this study were 59 respondents. The sampling technique is total sampling. Data analysis is by using Chi-Square Test. The results of the study showed that there was a significant relationship between independent and dependent variables. There is a correlation between family financial income and labor with the help of paraji (p = 0.001), there is a correlation between distance of residence and parajis’ health facilities (p = 0.000), and there is a relationship between indigenous customs and labor with the help of paraji (p = 0.000). It can be concluded that those three factors are extremely correlated to the labor with the help of paraji.